Shape memory properties of poly(methyl methacrylate-co--2-hydroxyethyl methacrylate)/poly(ethylene glycol) complexes - Liu, G.; Xie, D.; Li, Y.; Zhang, Y.; Huang, F. (Polimery, 2013)
Poly(methyl methacrylate-co-2-hydroxyethyl methacrylate) [P(MMA-co-HEMA)] networks and linear poly(ethylene glycol) (PEG) can form complexes, which show shape memory properties due to a large difference in storage modulus (E') below and above its glass transition temperature (Tg). The morphology of prepared samples was analyzed using transmission electron microscopy (TEM) and X-ray diffraction (XRD) analysis. Differential scanning calorimetry (DSC) was used to investigate the thermal properties and dynamic mechanical analysis (DMA) to determine the effect of temperature on the mechanical properties. It was found that the shape recovery ratio could reach 98 %.